2021
DOI: 10.1186/s12872-021-01926-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinically inapparent right heart dysfunction is associated with reduced myofilament force development in coronary artery disease

Abstract: Background Right ventricular dysfunction after CABG is associated with poor peri- and postoperative outcomes. We aimed to identify clinical and experimental predictors for preoperative inapparent right ventricular dysfunction and therefore hypothesized that reduced myofilament force development as well as altered levels of biomarkers might predict inapparent right ventricular dysfunction. Methods From 08/2016 to 02/2018, 218 patients scheduled for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, after thoracic surgery, there were no changes in diastolic or systolic RV function, which were observed after heart surgery with pericardiotomy [ 24 ]. In patients with a mild reduced preoperative RV systolic function, a significant impairment of the contractile apparatus was observed when it was assessed using an experimental model of right atrial fibers [ 25 ]. Therefore, it is not surprising that this disturbance increased in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, after thoracic surgery, there were no changes in diastolic or systolic RV function, which were observed after heart surgery with pericardiotomy [ 24 ]. In patients with a mild reduced preoperative RV systolic function, a significant impairment of the contractile apparatus was observed when it was assessed using an experimental model of right atrial fibers [ 25 ]. Therefore, it is not surprising that this disturbance increased in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in patients with CAD before CABG, predictors of mild RV systolic dysfunction, in addition to low LV ejection fraction [ 25 , 26 ], were also carbohydrate metabolism disorders, arrhythmias, an increased risk of surgery according to the EuroScore II scale, as well as a decrease in kidney function [ 25 ]. At the same time, the localization and number of coronary stenoses and the localization of a previous myocardial infarction did not affect the frequency of detection of the right heart dysfunction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that the resection of the LAA is part of SEIDC trial performed in our institution with prospective patient inclusion and all the surgeons followed this protocol. We analysed the patients enrolled in trial regarding the clinical aspects and consequences of LAA amputation [ 11 13 ]. The study was approved by the University Hospital ethics committee (IRB approval: 143/17-sc 6.10.2017).…”
Section: Methodsmentioning
confidence: 99%